Application of digital image correlation for the study of strain concentrations due to change in geometry in weld beads: parent interface of structural steel welds. (16th November 2016) - Pérez Fernández, J. Á.; Coppieters, S.; Debruyne, D.
Abstract : The paper aims to characterise the strain concentration of welded junctions subjected to elastic loads using digital image correlation (DIC). When measuring such small strains and heterogeneous strains fields with DIC, a compromise between noise and accuracy arises where a suitable choice of the image processing settings becomes crucial to obtain accurate results. An extensive study of the influence of the different processing parameters was carried out to ensure the best trade-off between accuracy and noise. A practical application was later performed with the found optimal settings; welded specimens were subjected to uniaxial and biaxial loads to assess possible influence of the strain state on the strain concentration. Results show a great variability of the strain concentration along the weld bead base, evidencing a significant influence of local geometrical characteristics. On the other hand, the strain state influence was found to be moderate, or almost inexistent for lower strain concentrations.